Optimization of Black Orchid (Coelogyne pandurata Lindl.) Extraction Using Simplex-Centroid Design for Total Phenolics, Flavonoids, and Antioxidants - Pebra Heriansyah; Novian Liwanda; Waras Nurcholis (Jurnal Jamu Indonesia, 2026)
Coelogyne pandurata Lindl., a black orchid endemic to Kalimantan, contains valuable antioxidant compounds. This study optimized its extraction using a Simplex-Centroid Mixture Design with ethanol, methanol, and acetic acid as solvents. Responses evaluated were total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity (DPPH). The highest TPC was obtained with 100% ethanol (2.52 mg GAE/g), TFC with equal parts of all solvents (6.41 mg QE/g), and antioxidant activity with 100% methanol (10.33 µmol TE/g). Ethanol yielded the optimal extraction condition, with verification values of 2.27 mg GAE/g (TPC), 3.42 mg QE/g (TFC), and 10.22 µmol TE/g (DPPH), and a desirability of 0.739. Although regression models were not statistically significant (p > 0.05), the results provide preliminary insights into solvent efficiency for extracting bioactive compounds. Further studies with expanded experimental designs and validation are required to enhance model accuracy and extraction reliability.